Communicating with many tongues: FOMC speeches and US financial market reaction - Bernd Hayo; Ali M. Kutan; Matthias Neuenkirch (Philipps-University Marburg, Faculty of Business Administration and Economics, 2008)
This paper studies the effects of FOMC communication on U.S. financial markets' returns and volatility using a GARCH model over the period from 1998 to 2006. We build a new data set that includes information on all FOMC speeches, post-meeting statements, monetary policy reports and testimonies. Our results can be summarized as follows: first, the impact on both returns and volatility is larger if the communication channel is more formal. However, since speeches happen much more often than other forms of communication, their absolute aggregate effect on financial markets is economically significant. Second, the effects of Fed communications tend to follow some sort of hierarchy: the Board of Governors (BoG) members have a greater impact than regional presidents, the chairman and vice chairman more influence than other BoG members and voting regional Fed presidents affect markets more than non-voting ones. Finally, news agencies appear to perform the role of a filter for financial market actors, who react more to newswire reports than actual speeches.
Keywords: E52; G14; 330; Central bank communication; central bank speeches; Federal Reserve; financial markets; monetary policy